Idiopathic Intracranial Hypertension - Cuellar, Hugo; Shah, Rahul (Seminars in Interventional Radiology, 2025)
Idiopathic intracranial hypertension (IIH) is a not well-understood syndrome of raised intracranial pressure, with a disproportionately higher incidence in obese women. This article summarizes the epidemiology and clinical features, and the diagnostic evaluation and management options of IIH, with a focus on venous sinus stenting as a promising treatment option.With growing obesity levels, IIH incidence has shown a commensurate increase globally. Our understanding of the pathophysiology of this condition continues to remain limited. Diagnostic modalities and criteria have evolved over the years with better imaging technology. Symptom management and preservation of vision form the cornerstone of most treatment strategies. Acetazolamide and topiramate are the first-line drugs of choice for medical management. Surgical interventions are essential in medically refractory cases or in cases of fulminant IIH. Sinus venous stenting is growing in popularity as a safe and effective surgical alternative.There exists a dearth of randomized controlled trials to guide our treatment strategies in patients with IIH. Although Venous sinus stenting offers a safe and effective treatment option in medically refractory cases, variability in various aspects of the procedure is extensive.
Keywords: IIH; venous stenting; papilledema